Efficacy and safety of vibrating capsule for functional constipation (VICONS): A randomised, double-blind, placebo-controlled, multicenter trial. (May 2022) - Zhu, Jia-Hui; Qian, Yang-Yang; Pan, Jun; He, Chen; Lan, Yu; Chen, Wei-Na; Wang, Bang-Mao; Zhao, Wei; Li, Jing-Nan; Li, Xiao-Qing; Lv, Bin; Fan, Yi-Hong; et al.
Summary: Background: Functional constipation (FC) is an intractable disease that carries large financial burden as well as emotional and physical stress. We aimed to assess the efficacy and safety of the newly developed smartphone-controlled vibrating capsule (VC) in patients with FC. Methods: From December 2018 to February 2020, we did a multicenter, blinded, placebo-controlled randomised trial in six top general hospitals in China focusing on patients aged 18 to 80 with FC. Patients were randomly assigned in a 1:1 ratio to receive VCs or placebo treatment for six weeks (two capsules per week) after a two-week baseline period. The primary outcome was the responder rate, defined as the proportion of patients with an increase of at least one complete spontaneous bowel movement (CSBM) per week during treatment compared to baseline in the full analysis set. This trial is registered with ClinicalTrials.gov, number NCT04671264, and is completed. Findings: 107 patients aged from 18 to 74 were randomly assigned to receive VC ( n  = 53) or placebo treatment ( n  = 54). The responder rate in the VC group was significantly higher than that in the placebo group (64·2% vs. 35·8%; difference, 27·7% [95% CI, 10·4–45·1]; P  = 0·005). More patients in the VC group reported weekly CSBMs ≥ 1 for at least four weeks during treatment (difference, 22·7% [95% CI, 8–46]; P  = 0·022) and follow-up period (difference, 17.3% [95% CI, 0–35]; P  = 0·048). The mean Patient Assessment of Constipation-Symptoms score and Patient Assessment of Constipation-Quality of Life score differed significantly from the baseline in both groups (all P  < 0·0001). The most common adverse event associated with VC was abdominal discomfort (3·7%). Interpretation: VCs can promote defecation, as well as ameliorating symptoms and improving the quality of life in patients with FC with sustained efficacy. VC appears to be a potential alternative physical treatment for FC with the exact mechanism and parameters warranting further investigation. Funding: The study was supported by "One hundred leading scientists for 21st century" of Health Department of Shanghai Municipal Government (to ZL, No.2017BR005).